2008
DOI: 10.1177/1753193408096022
|View full text |Cite
|
Sign up to set email alerts
|

Digital Oedema, Adhesion Formation and Resistance to Digital Motion after Primary Flexor Tendon Repair

Abstract: The development of digital oedema, adhesion formation, and resistance to digital motion at days 0, 3, 5, 7, 9 and 14 after primary flexor tendon repairs using 102 long toes of 51 Leghorn chickens was studied. Oedema presented as tissue swelling from days 3 to 7, which peaked at day 3. After day 7, oedema was manifest as hardening of subcutaneous tissue. The degree of digital swelling correlated with the resistance to tendon motion between days 3 and 7. At day 9, granulation tissues were observed around the ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Soft tissue oedema, the presence of flexor pulleys and adhesion formation would all contribute to resistance to tendon motion and thus influence tendon strength (Cao and Tang, 2009;Cao et al, 2008;Zhao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue oedema, the presence of flexor pulleys and adhesion formation would all contribute to resistance to tendon motion and thus influence tendon strength (Cao and Tang, 2009;Cao et al, 2008;Zhao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The chickens, weighing 1.5 to 2.5 kg each, were used as experimental models because they have a flexor mechanism similar to that of human digits and are a common model for studying the digital flexor tendon. [21][22][23][24][25][26] The chickens were anesthetized with an intramuscular injection of ketamine (50 mg/kg body weight).…”
Section: Methodsmentioning
confidence: 99%
“…18 -20 Cao demonstrated that the severity of postoperative edema is proportional to the increases in work needed to flex chicken digits. 19 The timing of the effects of edema has also been characterized, 20 including an early, substantial increase in resistance to digital motion; an intermediate period of higher resistance but no further increase in resistance; and a late period, characterized by the formation of adhesions. The results of these studies have led to recommendations regarding the most appropriate time to begin postoperative therapy.…”
Section: Discussionmentioning
confidence: 99%